2010
DOI: 10.1186/1471-2431-10-57
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-epidemiological profile and diagnostic procedures of pediatric tuberculosis in a tertiary care hospital of western Nepal-a case-series analysis

Abstract: BackgroundChanging epidemiology and diagnostic difficulties of paediatric tuberculosis (TB) are being increasingly reported. Our aim was to describe clinico-epidemiological profile and diagnostic procedures used for paediatric TB.MethodsA retrospective case-series analysis was carried out in a tertiary care teaching hospital of western Nepal. All pediatric TB (age 0-14 years) patients registered in DOTS clinic during the time period from March, 2003 to July, 2008 were included. Medical case files were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
13
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
(20 reference statements)
7
13
1
Order By: Relevance
“…results were similar to those of other studies, such as in Uganda 18 and Nepal, 19 in which .50% of children hospitalized with TB had EPTB. This high proportion of EPTB in children may be due to their immature immune systems: TB often progresses rapidly from infection with MTB to disease.…”
Section: Figuresupporting
confidence: 82%
See 1 more Smart Citation
“…results were similar to those of other studies, such as in Uganda 18 and Nepal, 19 in which .50% of children hospitalized with TB had EPTB. This high proportion of EPTB in children may be due to their immature immune systems: TB often progresses rapidly from infection with MTB to disease.…”
Section: Figuresupporting
confidence: 82%
“…20 The most common location for EPTB in our study was TBM (38.8%) followed by DTB (31.3%). In contrast, other studies 10,19 have reported that the lymph nodes are the leading presentation for patients with EPTB. The difference may lie in our study being a hospital-based series of pediatric TB patients who are likely to be more ill than those diagnosed as outpatients and may therefore have higher rates of severe TB (TBM and DTB).…”
Section: Figurementioning
confidence: 43%
“…These findings are on par with findings of Sreeramareddy et al who also reported same risk factors association in his study. 16 Fever was the most common presenting complaint in both PTB and EPTB in Present study followed by cough, loss of appetite and weight which is also reported in many studies globally. However, few studies reported cough, loss of appetite and weight as most common features in pulmonary tuberculosis.…”
supporting
confidence: 64%
“…[12][13][14] We observed that lymph node was the most common extra pulmonary site which has been affected by TB; Arora VK et al, Gocmen A et al, Ramesh et al and Sreeramareddy et al also shown similar findings as current study. 5,7,15,16 In the present study 83.87% patients completed the DOTS treatment, 10.75% were cured, so treatment success was seen in 94.60% of total cases. Various studies done by Sharma S et al, Satyanarayan et al, Arora VK et al and Indumati CK et al also DOTS treatment success rate more than 94%.…”
Section: Discussionmentioning
confidence: 81%
“…6 Similarly Sreeramareddy et al and S Shrestha et al observed similar symptoms in patients of their respective study. 7,8 We noticed history of contact with TB infection in 39% of patients while 61% had no history of contact with TB; a study conducted at ICH Chennai by Vijayasekaran et al has shown history of contact in 30.4% of patients, while Vimlesh seth et al study had shown positive contact history in 19% of children.…”
Section: Discussionmentioning
confidence: 97%